On the near-surface atmospheric circulation in the region of the Antarctic Peninsula - Tymofeyev, V.; Beznoshchenko, B.; Shcheglov, O. (Ukrainian Antarctic Journal, 2017)
The main objective of the research is to analyze the near-surface wind regime in accordance with the data from Ukrainian Antarctic Akademik Vernadsky station and compare it with the state of the atmosphere circulation in order to supplement knowledge of the regional climate. Traditional methods of climatological processing, correlation analysis were used. According to the data of Vernadsky station, there is an increase in surface wind speed in conditions of air temperature rise. The statistical inhomogeneity in the wind speed series is detected. The main conclusion is that the air temperature growth and the increase in surface wind speed is a single manifestation of climate change in the region of the study that reflects changes in atmospheric circulation, intensification of westerly and deepening of cyclogenesis in Antarctica.